The impact of high solar power penetration on load profile of Singapore power - Liu, Yongheng (2018)
With the growing of global energy shortage and environments pollution, exploiting renewable energy and new green source is necessary to achieve sustainable development. Solar energy is one of the most abundant, cleanest and most promising renewable source in the word. Solar photovoltaic grid connected technology have become the main form of the PV application. With the growing of capacity, PV system have impact on power system, meanwhile bring series of problem to system operation, this project discusses the impact of PV system on load profile including of flow, voltage and relay protection. Firstly, the grid-connected model is studied in this project, the grid-connected PV system which includes photovoltaic array, maximum power point tracking module, inverter module is established, and simulation results show the effectiveness of PV array, MPP control algorithms and the system model; the impact of PV system on power flow and voltage profile of distribution network are analyzed the impact rule of power flow and voltage profile according to the different positions, capacity and working states are studied by simulation using the PSIM, the technical measures and control strategies are proposed. Analyzing the characteristics of PV system, the degree of fault currents is studied by simulation using the PSIM, and the impact of different interconnecting locations, different capabilities and different fault points of PV system on short current and relay protection are analyzed, the different strategies are taken for this.